Speech and Language Dysfunction and Focal Epileptiform Activity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The medical history, EEG recordings, and developmental milestones of 19 children with speech and language dysfunction, and focal epileptiform activity were analyzed for prognostic risk factors in a study at University of Gothenburg, Sweden.